Code Switching Used by Cinta Laura in Daniel Mananta’s YouTube Channel - Andreas Fredick Geovano Soplanit; I Gusti Ngurah Parthama; Novita Mulyana (CV. Ulil Albab Corp, 2023)
Code switching is a part of sociolinguistics phenomenon that shows alterations of languages in a conversation or between utterances. Individuals that perform code switching can be deemed bilinguals. This study conducted research based on an event in online video platform, YouTube, that involves Cinta Laura as one of the speakers. The aims of this study were to identify the types of code switching and to explain the reasons of code switching by Cinta Laura in Daniel Mananta’s YouTube channel. The study examined Cinta Laura's code switching on Daniel Mananta's YouTube channel. Three types of code switching were identified: intra-sentential (10 data) and inter-sentential (10 data) switching were most common and tag switching (4 data). Six reasons for code switching were found, with talking about a specific topic being the most frequent (9 data), followed by being emphatic (5 data), interjections (4 data), repetition for clarification (3 data), quoting someone else (2 data), and clarifying speech content (1 data). Expressing group identity through code switching was not observed in Cinta Laura's utterances.